Immune adaptation to chronic intense exercise training: new microarray evidence - Liu, D.; Wang, R.; Grant, A. R.; Zhang, J.; Gordon, P. M.; Wei, Y.; Chen, P. (BMC Genomics, 2017)
Background: Endurance exercise training, especially the high-intensity training, exhibits a strong influence on the immune system. However, the mechanisms underpinning the immune-regulatory effect of exercise remain unclear. Consequently, we chose to investigate the alterations in the transcriptional profile of blood leukocytes in young endurance athletes as compared with healthy sedentary controls, using Affymetrix human gene 1.1 ST array.